Return period analysis of extreme rainfall events - GOYAL, S. C.; KATHURAI, S. N. (MAUSAM, 1984)
The return periods analysis of extreme events of rainfall for selected 15 stations of Krishna river basin have been studied and presented in this paper. The annual one-day rainfall data for 60-years (1901-60) was used for the study. The rainfall estimates were computed for different return periods using tow different distribution and Fisher & Tipett type II distribution. Return periods corresponding to highest recorded rainfall were interpolated for both the distributions. Results show that while Gumbel’s distribution seems to indicate very high return periods of extreme events, the Fisher & Tipett type-II distribution provides lower estimates of the recurrence interval. As rainfall events are randomly distributed in nature, the return periods of outliers should also be determined with reasonable accuracy. The present study shows that the rainfall estimates for different return periods as obtained by using Fisher & Tipett type II distribution technique are much higher than those obtained by using Gumbel;s technique. It is suggested that Fisher & Tipett type II distribution may be preferred for evaluating the return periods of extreme rainfall events to Gumbel distribution.